The Relationship Between A History of Exclusive Breastfeeding and the Development of Babies Aged 6-12 Months - Paninsari, Debora; Wau, Yesdita Rohanita; Barus, Elfriza Putri; Debora, Debora (GLOBAL HEALTH SCIENCE GROUP, 2024)
Having healthy children who develop well according to their age is every parent's dream. Breastfeeding babies from an early age is the right decision because breast milk is the best food for babies. To find out the relationship between the history of exclusive breastfeeding and the development of babies aged 6-12 months. Mother's milk (ASI) is the main source and must be given to all babies. To achieve optimal growth and development, babies should be given exclusive breast milk. until the age of six months and may continue until the child is 2 years old. The aim of the research is to determine the relationship between a history of exclusive breastfeeding and the development of babies aged 6-12 months In this research, we use a type of quantitative research that is analytical surveys. In this study, the crazy approach is Cross Sectional. The sampling used in this study is Total Sampling by taking samples of the entire population of mothers who have babies aged 6-12 months. Data collection techniques use questionnaires then data is analyzed with bivariate analysis and univariate analysts. The results of the chi-square test research with a probability value of ɑ = 0.05, from the research results it is known that the p-value is 0.040 ˂ from the value of ɑ 0.05, which can be concluded that there is a relationship between the history of breastfeeding and the development of the baby.